The Regulatory Role of Respiratory Tract Normal Flora (Corynebacterium spp) on Streptococcus pneumoniae Infections - Dutta,Shritama (2022)
Respiratory tract infections (RTIs) pose severe threats to global health. The microbial profile of the respiratory tract largely impacts their ecological niche. Epidemiological studies indicate that nasopharyngeal colonization of commensals like Corynebacterium spp is associated with reduced rates of RTIs, but the underlying mechanisms are undefined. Besides, most pathogens like Streptococcus pneumoniae asymptomatically colonize the mucosa of healthy individuals by forming biofilms. However, in response to extrinsic reasons, such as concomitant virus infections, bacteria disseminate from the biofilms, leading to a transition from asymptomatic carriage to disease/infection. Here, we studied the commensal-host and commensal-pathogen-host interactions between two clinical corynebacterial isolates Corynebacterium propinquum and Corynebacterium pseudodiptheriticum with the pathogen Streptococcus pneumoniae. By standardizing the single-species biofilm formation and assessment through antibiotic sensitivity assay and Scanning Electron Microscopy, we concluded that an epithelial substratum (live or pre-fixed) encourages the formation of mature, finely structured and consolidated corynebacteria biofilms, instead of abiotic surfaces, thereby contributing to its mutualistic relation with the host. Upon inclusion of pathogenic pneumococci in this system, we further demonstrated that in in vitro dual-species interaction models, corynebacteria reflect a somewhat protective property towards pneumococcus. We also investigated the host inflammatory responses (by studying NFκB and ERK signalling pathways) to corynebacteria alone and in combination with the pneumococcus, but due to experimental limitations were unable to annotate a conclusive remark on the inflammatory sensitization (if any) by corynebacteria on the epithelial cells for the immunomodulation of successive pneumococcus stimulations. A better understanding of the microbe-microbe and host-microbe interplay responsible for maintaining the nasopharyngeal microbial homeostasis is required to combat severe RTIs and withstand the ever-increasing antibiotic resistance. Thus, novel means of therapeutics can be identified by exploiting the modulatory role of corynebacteria on pneumococcus invasions by either protecting the host against colonization of pathogens or by improving the inflammatory response against pathogens invasions.